Etos Kerja Pengikut Tarekat Qâdirîyah wa Naqshabandîyah - Saifullah, Moh. (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2012)
This article examines the dimensions of Sufism doctrines adhered by the followers of tarekat Qâdiriyya wa Naqshbandiyya at pesantren Suryalaya Area Coordinator East Java in Surabaya. The questions to be asked are to what extent are these followers consistent in practicing the teachings of Sufism and actively engaged in socio-religious activities, and how are spiritual, material, and social life of the members of tarekat Qâdiriyya wa Naqshbandiyya Suryalaya? The study found that the teachings of Sufism practiced by the members of TQN are actually appropriate or consistent with the teachings of Islam. Therefore, it is not true for anyone to understand that Sufism doctrines can weaken people?s work ethic and make them poor and backward. This is because Sufism is, basically, able to strengthen the work ethic and spirit. In other words, people who engage in certain tarekat would be regarded as having misunderstanding toward its doctrines when they become spiritless, lazy, and undisciplined.